Activity of Bisbenzimidazoles Derivatives to Staphylococcus epidermidis - ALGUL, OZTEKIN; DURAN, NIZAMI (Asian Journal of Chemistry, 2010)
Biomaterial-associated infections, most frequently caused by Staphylococcus epidermidis and Staphylococcus aureus, are of increasing importance in modern medicine. The most important factor in the pathogenesis of biomaterial-associated staphylococcal infections is the formation of adherent, multilayered bacterial biofilms. The aim of this study was to synthesize bis(benzimidazole) derivatives and evaluate their in vitro antimicrobial activity against the growth of gram positive (Enterococcus faecalis, methicillin resistant S. aureus, methicillin sensitive S.aureus, S. epidermidis and S. epidermidis RP12 (slime producing), gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa) and pathogenic fungi (Candida albicans, Candida krusei, Candida parapsilosis, Candida tropicalis and Candida glabrata). The antimicrobial activity of bis(benzimidazole) derivatives was higher in gram positive bacteria. Bis(benzimidazole) derivatives were inhibited gram positive bacteria at the concentration range of 12.5-100 μg/mL. All compounds were shown to be bacteriostatic as well as bacteriocidal for cultures of S. aureus and S. epidermidis strains, regardless of their antibiotic susceptibility profile. This was demonstrated by using simultaneously the optical density measuring method and 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide-reduction assay. The highest activity was shown by 1,2-di(1H-benzo[d]imidazol-2-yl)ethane which demonstrated interesting activity regarding its effect on 24 h old staphylococcal biofilm cells viability.